Contribution of HLA Genes to Genetic Predisposition in Diffuse Panbronchiolitis - KEICHO, NAOTO; TOKUNAGA, KATSUSHI; NAKATA, KOICHIRO; TAGUCHI, YOSHIO; AZUMA, ARATA; BANNAI, MAKOTO; EMI, MITSURU; OHISHI, NOBUYA; YAZAKI, YOSHIO; KUDOH, SHOJI (American journal of respiratory and critical care medicine, 1998)
Diffuse panbronchiolitis (DPB) in East Asia is a distinctive chronic obstructive pulmonary disease of unknown etiology. We hypothesize that the disease susceptibility is due to genetic predisposition unique to Asians. Association between human leukocyte antigen (HLA)-Bw54 and the disease was previously reported. In the present study, using newly developed polymerase chain reaction (PCR)- based methods, we directly analyzed HLA class I and II alleles in 76 Japanese patients. HLA-A, -B, and -C antigens were screened by the conventional typing method, and then B22-group alleles including HLA-B54 were genotyped by single-strand conformation polymorphism analysis. Alleles of HLA-DRB1 gene were fully determined by the microtiter plate hybridization method. Thirty-seven percent of the patients possessed HLA-B*5401 allele conserved predominantly in East Asians, as compared with 15% of 110 healthy volunteers (chi2 = 12.4, p = 0.0004). In addition, 4% of the patients possessed B*5504 also unique to Asians but a rare allele which was not found in normal control subjects in this study. Typing of HLA-DRB1 class II gene did not demonstrate strong positive association with the disease. A33, B44, and DRB1*1302 showed negative association with the disease. We conclude that distinctive molecular structure of HLA-B alleles or a closely linked gene in the HLA region contributes to genetic predisposition in diffuse panbronchiolitis. This may partly explain why this disorder is found primarily in Asians.